Wholeness and internal relatedness: a Bradleyan critique of recent holistic metaphysics - Briceño Domínguez, José Sebastián (2015)
According to David Lewis’ influential thesis of Humean Supervenience, the world is a plurality of self-contained individuals standing in external relations of spatiotemporal distance. In the last decades, this thesis has been under attack by what I call ‘holistic ontologies’, the most salient of which are Dispositional Essentialism, Ontic Structural Realism, Priority Monism, and Existence Monism. These reactions obey different but closely related suspicions against the central features of Humean Supervenience. On one hand, there are suspicions against the idea of external relations; on the other hand, there are suspicions against the idea of self-contained plurals. Common to these holistic ontologies is to conceive the world not as an externally related heap but, in different degrees of strength, as an ‘internally related whole’. This work, following Bradley’s stance against relations, puts under critical scrutiny the merits of these holistic ontologies. The central aims are to make explicit the different senses of ‘wholeness’ and ‘internal relatedness’ that they happen to endorse; make explicit their internal flaws; and show the relative superiority of Existence Monism. As it happens, Existence Monism vindicates Bradley’s core ideas about relations, namely: that external relations are unable to relate; that internal relations are inherently unstable; and that all relations–external and internal–are better understood as imperfect abstractions from a more substantial, non-relational, kind of unity. I conclude with some skeptical remarks against my own metaphysical preferences and against ontology in general.